Cine/Sine Spanish beginnings of Philippine cinema - Deocampo, Nick.; Center for New Cinema ([Quezon City] Center for New Cinema, 2012)
"This hour-long digital documentary recreates the beginning of motion pictures in the Philippines. By tracing the origin of cinema, it sheds light on Manila as the birthplace of motion pictures. Based on his award-winning book, Cine: Spanish Influences on Early Cinema in the Philippines, the documentary traces the beginning of cinema in 1897 when two Spaniards showed the first moving pictures in Escolta. Against the backdrop of war and revolution, film developed to become the emerging Filipinos' dominant form of public entertainment. Featured in the documentary are elements of Spanish culture found in Filipino films as evidenced through the classic films made by three National Artists - Eddie Romero, Lino Brocka and Ishmael Bernal. CINE/SINE is Deocampo's homage both to Philippine cinema and the Filipino nation that is its twin."--Center for New Cinema Website.
Library has: VDR-1660 (1 DVD)
DVD
In English.
Keywords: Motion pictures -- Philippines -- History